Epidemiology, mechanisms and prevention of electric scooter-related injuries with particular emphasis on the pediatric population - a narrative literature review - Modelska, Julia; Jeleń, Anita; Podolska, Anna; Paluchowicz, Karolina; Siwicka, Katarzyna; Szewczyk, Konrad; Janasik, Laura; Kociucka, Patrycja; Sadowski, Krzysztof (Quality in Sport, 2026)
Background: Over the past decade, electric scooters have become a common element of urban micromobility, offering a convenient and environmentally friendly alternative to short-distance car travel. However, the rapid growth in the number of users has not been supported by parallel infrastructure development or consistent legal regulations, leading to a growing number of injuries related to their use. These incidents place a growing burden on healthcare systems, particularly emergency departments and trauma surgery. Aim: The aim of the study was to review the current literature on epidemiology, accident mechanisms, types and locations of injuries, and strategies for preventing injuries related to the use of electric scooters, with particular emphasis on the pediatric population. Materials and methods: A narrative literature review was conducted using the PubMed and Scopus databases. Studies on e-scooter-related injuries were analyzed, including epidemiological data, injury mechanisms, risk factors, anatomical injuries, and preventive measures. Results: Available research indicates a rapid increase in the number of injuries associated with e-scooter use in various regions of the world. Young adults are the most injured group, but children and adolescents are at increased risk of serious injury. The predominant mechanism of injury is falls without the involvement of other road users. The most common injuries are head and facial injuries, as well as upper limb fractures. Failure to wear a helmet, driving under the influence of alcohol, driving at night, and excessive speed are the main risk factors. Conclusions: Injuries related to e-scooter use constitute a significant and growing public health challenge. Effective prevention requires comprehensive measures encompassing legal regulations, user education, infrastructure improvements, and the implementation of technological solutions.